Assessment of The Needs of Physicians Working in Cosmetic Medicine Field on Libya: Toward A Safe Clinical Practice - Hajer Elkout; Abdulhakim Oun (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objectives. There are many barriers to the practice of safe and professional cosmetic medicine with physicians trying to attend workshops and training sessions individually to attain knowledge to meet the demands of cosmetic medicine. This study was designed to explore the current trend and to assess physicians’ needs for knowledge, skills toward safe cosmetic medicine practice in Libya. Methods. A cross-sectional survey was conducted online amongst physicians practicing surgical and non-surgical cosmetic medicine procedures between 1st to 21st April 2020 using questionnaire consisting of 20 questions. Results. A total of 104 doctors working in the cosmetic surgical and non-surgical field responded to the questionnaire. Approximately 90 were females and 14 males and 88% were young professionals aged 45 years or younger. About two thirds of the respondents are new in the cosmetic practice with 3 years or less experience, yet, 97 (93.3%) had a formal training in cosmetic medicine and 68 (65.4 %) continued to receive technical support from their trainers. All of the respondents expressed their desire for further training in different areas of cosmetic medicine. Almost half of the included physicians also stated that they still hesitate while performing clinical procedures despite of having hands on training. Conclusions. The current study highlights the importance of establishing routine assessment of needs among doctors practicing cosmetic medicine. The results of this survey may assist training programs in determining training needed during both medical training and professional training courses.